Learning from mothers' success in breastfeeding maintenance: coping strategies and cues to action - Liao, Qiuyan; Yuan, Jiehu; Lok, Kris Yuet Wan; Ngu, Siew Fei; Chen, Yuyi; Lam, Wendy Wing Tak (Frontiers in Psychology, 2023)
This study aimed to gain insight from mothers who were successful in breastfeeding maintenance to develop interventions for promoting breastfeeding maintenance. Following the phenomenological framework, this qualitative study recruited mothers who had maintained breastfeeding for at least 4 months for in-depth interviews. A total of 30 in-depth interviews were completed. We found that almost all participants had experienced an initial adjustment period. During this period, a social support network, personal perseverance in “trying” breastfeeding and “pumping,” and adjusting expectations for breastfeeding to relieve themselves from the pressure of exclusive breastfeeding were important coping strategies. All participants then entered a stage of getting more attuned when breastfeeding was easier. During this period, seeking support from the online mother groups, deliberating medication that might affect breastfeeding, adjusting to accommodate breastfeeding and lives, and managing breastfeeding in public were the main strategies. For working mothers, despite workplace and employers' support, proactive adjustment for using the facilities and lactation breaks for breast milk expression was essential for breastfeeding continuation after returning to work. Throughout the whole journey, positive cues identified from their breastfeeding experiences that helped breastfeeding maintenance included enjoying breastfeeding, breastfeeding as a personal achievement, a healthy and thriving child, positive social feedback, bodily response, the convenience of breastfeeding, and breastfeeding as a motherhood commitment. To conclude, while mothers should be mentally prepared for the difficulties of breastfeeding, they should also be encouraged that things will always get easier as they persevere. Adjustments should be made to accommodate lives and other personal needs. Future studies should consider integrating relevant cues into existing psychosocial interventions for promoting breastfeeding maintenance.